2021
DOI: 10.3390/ijerph18031328
|View full text |Cite
|
Sign up to set email alerts
|

Youth Sports Participation Is More Important among Females than Males for Predicting Physical Activity in Early Adulthood: Iowa Bone Development Study

Abstract: A gender difference in youth sports and physical activity participation is well documented. However, research is limited to understand potential gender difference in the long-term effects of youth sports participation. The study aim was to compare the likelihood of meeting the aerobic Physical Activity Guidelines (PAG) in early adulthood by youth sports participation patterns among females and males. The study sample included 582 Iowa Bone Development Study participants (Iowa, USA). Participation in organized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…According to several research, children and adolescents can benefit from participation in sports ( 3 5 ). Specifically, the Iowa Bone Development Study indicated that sports participation could predict later sufficient physical activity ( 6 ). Several recently published research articles using longitudinal design have demonstrated a potentially negative association between greater sports participation and fewer symptoms of depression and anxiety in adolescents ( 1 , 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to several research, children and adolescents can benefit from participation in sports ( 3 5 ). Specifically, the Iowa Bone Development Study indicated that sports participation could predict later sufficient physical activity ( 6 ). Several recently published research articles using longitudinal design have demonstrated a potentially negative association between greater sports participation and fewer symptoms of depression and anxiety in adolescents ( 1 , 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Australian pre-adolescents, there was high amount of MVPA among children with higher socio-economic status [ 41 ]. Similarly, in US children, boys and girls with higher household income were 2.0 and 2.6 times more likely to achieve physical activity guidelines during adulthood, respectively [ 42 ]. Children with low socio-economic status generally have low participation in school and community sports activities [ 43 ], though not habitual MVPA as measured by accelerometery.…”
Section: Discussionmentioning
confidence: 99%
“…The summary above concerns associations between sports club participation and MVPA only, not associations with trajectories of MVPA and/or sedentary behaviour. We are only aware of a single study that attempted to examine associations between sports club participation in children and adolescents and MVPA trajectory, and that study did not consider sedentary behaviour trajectory [ 42 ]. That study investigated sports participation trajectories in US youths from 6 to 18 years and found three distinct groups, the continuously participating group was 45.9% and dropouts from sports participation occurred mostly between 9 to 13 years [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…MVPA minutes were calculated by summing MPA minutes and VPA minutes. In addition, because in the adult PAG (i.e., ≥ 150 min/ week of MPA, ≥ 75 min/week of VPA, or an equivalent combination of MPA and VPA) [1,2], one minute of VPA is considered to be equivalent to two minutes of MPA, we calculated MPA-equivalent minutes (minutes/day) at age 22 years by summing MPA minutes and twice VPA minutes (MPA minutes + 2 × VPA minutes) [28].…”
Section: Exposurementioning
confidence: 99%